Application of Knowledge Sharing at UPT Puskesmas Desa Medan Krio - Abdi Mubarak Syam (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2022)
Objective: This review aims to find a relationship between the increasing number of monkeypox cases, especially in LGBT community, based on the literature study approach and case reports. One of the non-medicamentous ways is to reduce travelling abroad, especially in countries with many monkeypox cases. Preventing direct contact, such as abstaining from sex and using condoms, is also a way to reduce the morbidity of monkeypox infection, especially in LGBT community. The treatment has not proven effective, and the available vaccines, especially in Indonesia, are still limited. Only a few cases in Indonesia have been reported. Method: This research is based on a literature study approach and case reports with article sources obtained from Eurosurveillance and Elsevier. It restricts articles using the keywords "cases that occurred in patients in the LGBT / MSM community" to get relevant data following the current monkeypox outbreak conditions. Result: The appearance of the monkeypox virus in 2022 in 58 countries and Indonesia is no exception, which confirmed 1 case in patients post travelling abroad. The current monkeypox infection is still present, with symptoms that vary from person to person and are typically characterized by reddish rashes. Still, it is primarily confined to the genital, perigenital, and perianal areas. It manifests at various stages of development, in addition to transmission from animals caused by hunting activities or in LGBT ( Lesbian, Gay, Bisexual, and Transgender) communities that have unprotected sex and can be infected through semen and saliva. Conclusion: Monkeypox cases that occur globally in 2022 need further research to reduce and prevent, especially in the LGBT community and those at risk of infection, pregnant women and babies, as well as medical personnel in close contact with patients. One of the non-medical procedures is reducing travel abroad, especially in countries with many cases of monkeypox, and reducing direct contact with sufferers, such as abstinence from sex and using condoms in the LGBT community, is also one way to reduce the morbidity of monkeypox infection. The treatment has not been proven effective, and the existing vaccines, especially in Indonesia, are still limited. Only a few cases in Indonesia have been reported.